Enhancing hovercraft energy performance: Adaptive lift fan control for optimal efficiency - Rezaei, Sajed; Parlak, Berke Ogulcan; Yavasoglu, Huseyin Ayhan (ELSEVIER, 2024)
As amphibious vehicles, hovercrafts glide over nearly frictionless surfaces thanks to a unique lift fan design that counteracts gravitational forces. However, this design leads to high energy consumption. Typically, hovercrafts operate their lift fan at maximum capacity or adjust it manually. This paper introduces an adaptive control method to mitigate a significant drawback of hovercrafts, which is excessive energy consumption stemming from their unique lift fan design. It discusses a methodology for identifying the most energy-efficient design, based on computational fluid dynamics analysis. Hovering and propulsion principles are addressed in detail to demonstrate the forces acting on the hovercraft and the motor selection process. This study's pioneering integration of adaptive and hysteresis controls for the lift fan represents a significant advancement in hovercraft energy management, offering a novel approach that markedly enhances operational efficiency and environmental sustainability. The paper proposes and evaluates various drive cycles to assess the control method's effectiveness and environmental impact. The results show that this approach can reduce energy use and, as a result, carbon emissions by up to 48.3 %.
Keywords: Hovercraft; Adaptive control; Hysteresis control; Drive cycle; Energy consumption; TRAJECTORY TRACKING; Science & Technology - Other Topics; Energy & Fuels